Clearing og afvikling i et retligt perspektiv - Niels C. Andersen (Danmarks Nationalbank, 2004)
– This paper describes how the two most important clearing and settlement systems in Denmark, VP and the Sumclearing, work in practice. Further it analyses, how the legal framework in the Securities Trading Act, STA, based on directive 98/26/EC on settlement finality in payment and securities settlement systems works in relation to the functionality of VP and the Sumclearing. The functionality for both systems encompasses net settlement (multilateral netting). The description of the two systems explains not only the multiple batches processing in the systems, but also the systems terms and conditions and the cash settlement in Danmarks Nationalbank. The conclusion is that both systems have entered into fully valid and binding agreements of multilateral netting with its participants according to the requirements in STA. Further the moments, when transfer orders become binding and irrevocable, are identified. In a separate section the important link established between VP Securities Services and Euroclear in Belgium is described, including an elaboration of the cross-system settlement of trades between participants of VP Securities Services and Euroclear, whereby Danish book entry securities electronically are moved to Belgium or back again. Finally the paper analyses what happens in case a participant of VP or the Sumclearing is declared bankrupt. The conclusion is that both VP and the Sumclearing are structured in a way, so the legal and practical consequences of a participant's bankruptcy are predictable in all standard cases. For the other participants this is crucial for the possibility to adapt to the situation. The bibliography contains a list of relevant homepages, and a glossary of some of the most important terms in the paper has been compiled.
Keywords: 330